Dual BACE-1/GSK-3β Inhibitors to Combat Alzheimer's Disease: A Focused Review - Rampa, Angela; Gobbi, Silvia; Concetta Di Martino, Rita M.; Belluti, Federica; Bisi, Alessandra (Current Topics in Medicinal Chemistry, 2017)
In industrialized countries, Alzheimer's disease represents the most devastating neurodegenerative disorder in elderly people and the search for a disease modifying agent is still justified by this unmet need. Several possible targets have been explored to find an appropriate drug therapy, and in this review, dual inhibitors of beta secretase and glycogen synthase kinase 3, recently reported in literature, will be appraised. Applying a ligand-based approach, the triazinone core emerged as a suitable scaffold to simultaneously bind the aspartic dyad of BACE-1 and the ATP site of GSK-3β, leading to a series of small molecules endowed with a balanced micromolar affinity and a promising pharmacokinetic profile. Differently, by means of a structure-based approach, a series of well-balanced dual binding molecules were designed, taking advantage of the versatility of the curcumin scaffold. For some of these new compounds a potential neuroprotective effect was also observed, due to their ability to counteract the oxidative stress through the inhibition of NQO1 enzyme. Finally, different virtual screening analyses were performed, leading to the identification of new potential scaffolds deserving further development.
Keywords: Neurodegenerative Diseases (ND)